Hubungan Komunikasi Petugas Kesehatan terhadap Kepatuhan Peserta Mengikuti Kegiatan Prolanis di Puskesmas Mojolangu Kota Malang - Agriva Langu; Frengki Apriyanto; Dwi Norma R. (Lembaga Pengembangan Kinerja Dosen, 2025)
Chronic disease problems in the community are often found, namely Diabetes Mellitus (DM) and blood pressure. The low level of participant compliance in Prolanis activities is caused by many factors, one of the factors that can influence it is the interaction or communication factor between health workers and Prolanis participants. The purpose of this study is to analyze the correlation of health worker communication to participant compliance in participating in Prolanis activities at the Mojolangu Public Health Center, Malang City. The design of this study was quantitative correlational with a Cross sectional approach and observational analytical methods. The population was all Prolanis participants at the Mojolangu Health Center, Malang City, as many as 82 people with a sampling technique using total sampling. The instruments used were a questionnaire on communication between health workers and participants and a checklist of participant attendance in participating in Prolanis activities. The statistical test used in this study was the Spearman rank test calculation. The results of the study showed that some respondents said that communication between health workers at the Mojolangu Community Health Center was in the good category, as many as 41 respondents (50.0%). Most respondents were compliant in participating in Prolanis activities at the Mojolangu Health Center, Malang City, as many as 45 respondents (54.9%) and there was a strong relationship between health worker communication and participant compliance in participating in Prolanis activities at the Mojolangu Community Health Center, Malang City (P = 0.000; r = 0.556). Based on the results of the study, it was concluded that there is a strong relationship between communication between health workers and participant compliance in participating in Prolanis activities at the Mojolangu CommunityHealth Center, Malang City.